Efficient removal of methyl orange from aqueous solutions using ulexite - HACIOSMANOĞLU, GÜL GÜLENAY; GENÇ, SEVAL; CAN, ZEHRA SEMRA (ELSEVIER, 2021)
Ulexite, a natural boron mineral was used as an adsorbent for methyl orange (MetO) removal from aqueous solutions. SEM/EDS, IEP, BET, XPS and FTIR analyses were used for the characterization of ulexite. The adsorption characteristics of MetO by ulexite were investigated using batch adsorption experiments with varying contact time, pH, initial dye concentration and temperature. Batch adsorption experiments showed that the equilibrium time was 90 min and the reaction kinetics followed pseudo-first-order model. Equilibrium adsorption data were best fitted by the Liu isotherm and the maximum amount of MetO adsorbed per unit weight of ulexite was 1477.6 mg/g (experimental) at 298 K. The equilibrium experiments were repeated for different temperatures (288, 298 and 308 K) and the obtained data were used to calculate the thermodynamic parameters. Based on the results, the adsorption process was exothermic, spontaneous and thermodynamically favourable under the experimental conditions. The adsorption mechanism was elucidated by SEM/EDS, BET, XPS and FTIR analyses of ulexite before and after MetO adsorption. These results suggested that adsorption mechanism includes pi-p bonding, electrostatic attraction, hydrogen bonding and OH-pi bonding. The reuse experiments demonstrated a 14.17 % reduction in the adsorbed amount of MetO per unit weight of ulexite, after the fifth adsorption-desorption cycle. The obtained results indicate that ulexite is potentially an efficient adsorbent for MetO, especially for high initial concentrations. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Methyl orange; Azo dye; Ulexite; Boron mineral; Pi-interaction; WASTE-WATER; ACTIVATED CARBON; DYES ADSORPTION; SYNTHETIC DYES; ADSORBENTS; CONTAMINANTS; COMPOSITES; CLAY